1998
DOI: 10.1080/17450399809381905
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different technical treatments of rapeseed on the feed value for broilers and laying hens

Abstract: The effect of different technical treatments of rapeseed on its feed value for broilers and laying hens was the object of the study. The technical treatments comprised different grinding procedures (whole seed, roller mill--coarse and fine adjustment, flake mill) resulting in different average particle sizes of the ground seed and thermal treatments of flaked seed (hydrothermal treatment, micronizer, jet sploder). Each thermal treatment was carried out at two temperatures. A marked increase in the digestibilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…Similarly, Huyghebaert (1997) found decreased fat digestibility when adding a carbohydrase blend to broiler diets, which might be a comparable process to our study. In contrast, Daenicke et al (1998) found that increasing the temperature of the thermal feed treatments resulted in an increase in crude fat digestibility.…”
Section: Discussionmentioning
confidence: 85%
“…Similarly, Huyghebaert (1997) found decreased fat digestibility when adding a carbohydrase blend to broiler diets, which might be a comparable process to our study. In contrast, Daenicke et al (1998) found that increasing the temperature of the thermal feed treatments resulted in an increase in crude fat digestibility.…”
Section: Discussionmentioning
confidence: 85%
“…Interestingly, application of heat to the barrel of the press during oil extraction increased the AID and ATTD of energy of cold-pressed canola cake. This increase could be due to increased lipid solubility because of heat application and, therefore, greater fat digestibility of pressed cake (Dänicke et al, 1998). Indeed, fat digestibility of cold-pressed canola cake followed the reduced energy digestibility of the nonheated barrel at slow screw speed.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, appropriate processing temperature is critical for the elimination of heat-labile anti-nutritional factors found in legume seeds. Extrusion has been to shown to have positive effects on the in vitro digestibility of protein (Alonso et al, 2000a;200b;El-Hady and Habiba, 2002) and the in vivo digestibility of fat (Danicke et al, 1998;Lichovnikova et al, 2004), amino acids (Lichovnikova et al, 2004) and starch (Alonso et al, 2000b) in diets for poultry. These improvements have been attributed to due to the reduction of anti-nutritional factors, denaturation of native protein and gelatinisation of starch.…”
Section: Introductionmentioning
confidence: 99%